Enforcement and cost-effectiveness of international environmental agreements: The role of side-payments - Carsten Schmidt (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1997)
The paper explores the prospects for international environmental cooperation in a context of limited enforcement, if we allow for side-payments between countries and sequential moves in the implementation of the agreement. The framework of the analysis is a static model of heterogenous countries formulated in terms of costs and benefits of emission abatements. Taking the noncooperative Nash equilibrium as starting-point for negotiations, a mechanism is analysed that uses self-financed transfers as an instrument to create and enforce an international environmental agreement. Two kinds of side-payments are considered: transfers that are self-financed but otherwise unrestricted, and transfers that are restricted to compensations for cost-effectiveness of abatements. Numerical simulations for the different scenarios considered illustrate the gains from cooperation that can be achieved with this mechanism.
Keywords: D61; D62; H77; Q20; Q28; 330; Internationale Umweltpolitik; Internationale Finanzhilfe; Spieltheorie; Kosten-Nutzen-Analyse; Theorie